Use of Image Media in Learning to Introduce the Concept of Number in Children 5-6 Years Old at Kindergarten - Nene, Lusila; Miranda, Dian; Amalia, Annisa (International Journal of Learning and Instruction (IJLI), 2023)
This study aims to determine the use of media images in learning to introduce the concept of numbers to children aged 5-6 years at Bruder Nusa Indah Kindergarten in Pontianak. This study used a descriptive qualitative method. The data source for this study was a teacher and group B2 children at the Bruder Nusa Indah Kindergarten. This research technique is observation using observation sheets, direct interview techniques using interview sheets and documentaries using documentation tools. Data analysis in this study is data collection, data reduction, presentation and conclusion/verification based on the results of the research that has been done. It is found that: 1). Planning to use image media in introducing the concept of numbers to children aged 5-6 years at Bruder Nusa Indah Kindergarten is carried out by determining a theme for the learning program to facilitate the process and become a guideline for the implementation of learning, from the predetermined theme it is made into RPPM, RPPH, tools and instructional Media. 2). The implementation of the use of media images in introducing the concept of numbers to children aged 5-6 years at Bruder Nusa Indah Kindergarten has been carried out by the teacher well during the research. The teacher carried out learning through three activities, namely initial activities, core activities, and closing activities, in accordance with what was planned. In implementing the learning, the teacher uses the singing method and the question-and-answer method and gives assignments in the form of children's worksheets and portfolios the implementation of learning using picture media in introducing the concept of numbers to children. 3). Evaluation of learning outcomes in introducing the concept of numbers to children aged 5-6 years at Bruder Nusa Indah Kindergarten is an action or a process of implementing learning to determine the value of children's learning success after going through the learning process. The teacher also directly observes the learning process by assessing children's work.  Keywords: Image Media, The Concept of Numbers, Kindergarten